Risk awareness on uterine cancer among Australian women - George, Mathew; Abu Asab, Nihad; Varughese, Elizabeth; Irwin, Matthew; Oldmeadow, Christopher; Hollebone, Keith; Apen, Kenneth; Renner, Stefan (Asian Pacific Journal of Cancer Prevention, 2014)
Uterine cancer is the most common invasive gynaecological cancer in Australia. Early detection is a key predictive factor achieved by increasing public awareness and participation in screening. This observational study measures awareness of gynaecological malignancies, particularly uterine, among women in two rural areas of New South Wales, Australia. Patients presenting to gynaecology clinics in January to March 2014 were invited to complete a structured questionnaire. Women with a history of cancer and incomplete questionnaires were excluded. Of the 382 patients invited to participate, 329 (86%) responded with complete feedback. Most respondents were younger than than 50 years (66%) and married with at least 2 children (74%). The majority (94%) of participants had no awareness of uterine cancer and many (46%) were unable to identify common risk factors including obesity, diabetes and hypertension. The ability to identify risk factors was correlated to age, marital status and obesity. The study identifies poor awareness on uterine malignancies in two typical areas of rural Australia. Although external validity is limited by sociological factors, poor awareness of uterine cancer among rural patients in this study represents a valid public health concern. It is imperative to improve awareness of uterine cancer and available screening programs to facilitate early detection and cure.
EVALuna2:17536